Recent synthetic methodologies for the tricyclic fused-quinoline derivatives. Issue 1 (2nd January 2021) - Saddique, Furqan Ahmad; Farhad, Muniba; Aslam, Sana; Ahmad, Matloob
Abstract: Tricyclic fused-quinoline ring system belongs to a fascinating and versatile class of heterocycles that demonstrates a wide spectrum of biological activities such as anti-malarial, anti-microbial, anti-viral, anti-cancer, analgesic, anthelmintic, cardiovascular, anti-hypoglycaemic, etc. Tricyclic fused-quinolines like pyrroloquinolines, pyranoquinolines, pyrimidoquinolines, furoquinolines, imidazoquinolines, pyrazoloquinolines, thienoquinolines, etc. can be synthesized via a number of efficacious synthetic routes that include mostly multicomponent reactions, transition metal catalysis, Lewis and Bronsted acid catalysis and microwave-assisted reactions. In this review, the focus has been placed on these methods along with various factors affecting yields, stereo- and regioselectivities of products and applications of these protocols to achieve valuable candidates reported during the last five years. Graphical abstract: